IKLAN ROKOK A MILD DALAM MEMBANGUN KONSTRUKSI REALITAS GAYA HIDUP REMAJA - Anggia Hasti Benjamin (Jurnal Pustaka Komunikasi, 2019)
This study aims to determine the advertisement of A Mild version of " Mula Mula Malu Malu Lama Lama Mau " to build or construct the reality of adolescent lifestyles after being studied with semiotics belonging to Ferdinand de Saussure. The theory used by the author in conducting this research is the Semiotics theory of Ferdinand de Saussure with the Constructivism research Paradigm using a Qualitative approach. The results of this study indicate that the meaning is created through the existence of arbitrary relationships between markers (signifier) as a description of the word with a sign (signified) which is a description of the concept of the audience's mind so that the negative meaning is created. Writing language is identified as a marker (signifier) because the writing language in this advertisement also contains emotional persuasive meaning that contains elements of sexuality. Visual design elements are identified by the author as signified because through this unit the concept picture is obtained by the audience so that the emergence of such meaning is implied through the gesture of the visual elements of the ad, namely male and female figures